Assessing the reactogenicity of Tdap vaccine administered during pregnancy and antibodies to Bordetella pertussis antigens in maternal and cord sera of Thai women. Issue 11 (7th March 2018) - Wanlapakorn, Nasamon; Maertens, Kirsten; Chaithongwongwatthana, Surasith; Srimuan, Donchida; Suratannon, Narissara; Vongpunsawad, Sompong; Tran, Thao Mai Phuong; Hens, Niel; Van Damme, Pierre; Locht, Camille; Poovorawan, Yong; Leuridan, Elke
Abstract: Introduction: Pregnant Thai women have low antibody titers against B. pertussis antigens, which coincide with an increasing incidence of pertussis among Thai infants. Thus, there exists a potential benefit of a booster dose of tetanus- diphtheria-acellular pertussis (Tdap) vaccine administered during pregnancy. Here, we report the vaccine reactogenicity profile and birth outcomes in Tdap-vaccinated pregnant women who have or have not had prior immunization with tetanus vaccine, and the IgG levels to B. pertussis antigens in maternal and cord sera at delivery. Materials and methods: Pregnant women (N = 370) aged 18–40 years were administered the Tdap vaccine (Boostrix®, GlaxoSmithKline, Rixensart, Belgium) at 26–36 weeks gestation. Adverse events following vaccination were identified by follow-up telephone call and medical record review. IgG against pertussis toxin (anti-PT), filamentous hemagglutinin (anti-FHA) and pertactin (anti-PRN) in both maternal and umbilical cord blood obtained at delivery were quantitatively evaluated using enzyme-linked immunosorbent assay (EUROIMMUN®, Lübeck, Germany). Results: There was no reported increase in the severity or duration of adverse events associated with the administration of an extra tetanus-containing vaccine within the previous five years (N = 181) or multiple doses of tetanus-containing vaccines during the current pregnancy (N = 98). Vaccination at least eight weeks prior to delivery resulted in high antibody titers to all B. pertussis antigens studied. Conclusions: The reactogenicity of Tdap vaccine administered during pregnancy was not affected by prior tetanus toxoid immunization. High transplacental antibody against B. pertussis antigens in the cord blood provides evidence of antibody transfer and should thus help to protect newborns from pertussis during early life.